Boron isotopes in tourmaline as a tracer of metasomatic processes in the Bamble sector of Southern Norway - Bast, R.; Scherer, E.; Mezger, K.; Austrheim, H.; Ludwig, T.; Marschall, H.; Putnis, Andrew; Lowen, K. (Springer, 2014)
The Bamble sector of southern Norway comprises metagabbros and metasediments that were metasomatically altered to various extents during a late stage of the Sveconorwegian orogeny (~1.06 Ga). The infiltration of highly saline brines along veins led to penetrative scapolitizationand albitization on a regional scale and the local deposition of Fe–Ti oxides. Typical secondary mineralassemblages include either scapolite + apatite + amphibole + phlogopite + tourmaline, or albite + epidote + calcite + chlorite + white mica, indicating that the fluids introduced large amounts of Na, Cl, Mg, Ca, K, P, and B to the system. Metasomatic tourmalines associated with different alteration stages as identified by variations in majorelement composition and initial 87Sr/86Sr were analyzedfor B isotopic compositions to constrain possible sources and the evolution of the hydrothermal fluid(s). Measured d11B values range from -5 to +27 ‰ relative to SRM-951, suggesting marine evaporites interlayered with various amounts of continental detritus and pelagic clay as a possible B source reservoir. The influence of a seawater-derived component is clearly indicated by the heavy B isotope signature of tourmaline related to Al–Mg-rich metapelites. In contrast, negative d11B values can be explained by the influence of pneumatolytic fluids associated with granitic pegmatites. On a regional scale (i.e., several km), d11B values in tourmaline vary widely, whereas variations within a single outcrop (tens of m) are typically small and can be ascribed to different generations of tourmaline related to several fluid pulses.